PENGARUH DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT SELARAS LAWANG SEWU JAKARTA - Idah Yuniasih; Teni Agustina; Rosento Rosento (Jurnal Marketing, 2019)
Employee performance very important for an organization, one of them is the purpose of employee performance is to improve the discipline of work employees so as to achieve the purpose of obtaining a good performance. The research was conducted to know the influence of discipline employees can be transferred to these pay rises on performance he would do to PT Selaras lawang Sewu Jakarta. Sample used is sample saturated with use likert scale, to measure the magnitude of variable influence is used test a correlation coefficient, test the coefficients determined and test the regression equation is linear simple with the help of application program computer IBM SPSS 21. Methods used in this research is observation, the questionnaire and documentation. Based on the results of data analysis done. That the value a correlation coefficient of 0,728 which means strong and had links positive between discipline of the performance of employees. Employee performance affected by the discipline to employee performance. Employee performance influenced by the discipline of 53% and the rest 47% influenced by other factors out research. The results of the regression equation of Y = 9,368 + 0,776X every unit and the X up by 0,776